PENILAIAN KINERJA KEUANGAN KOPERASI BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH (Studi Pada Koperasi Karyawan “Tunas Harapan” PT. Bentoel Prima Kabupaten Malang) - Ruby Rantina Febrianti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The objective of the study is to examine the financial performance of PT. Bentoel Prima's employee cooperative, Tunas Harapan, during the period of 2013 up to 2015. The research tool used to assess the financial performance is the Regulation No. 06/Per/Dep.6/IVl20l6 issued by the Supervision Deputy of the Ministry of Cooperatives and Small and Medium Enterprises. The regulation covers such research aspects as capital, productive asset, management, efficiency, liquidity, independence and development, and cooperative's identity. This descriptive research attempts to explain the financial performance of the employee cooperative Tunas Harapan with the cooperative's accountability report as the primary data source. The data are collected by document study and interview. The collected data are further analyzed by the ratios contained in the tools. The result of analysis illustrates that the financial performance of PT. Bentoel Prima's employee cooperative Tunas Harapan is